PENGARUH GREEN ACCOUNTING TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR PERTAMBANGAN DAN PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuliana Vanduwinata; Erik Nugraha; Sukadwilinda Sukadwilinda; Indri Gustirani (Universitas Sangga Buana, 2025)
This study aims to test and analyze the influence of Green Accounting on profitability in mining and agricultural companies listed on the Indonesia Stock Exchange. The sample in this study uses a purposive sampling method, data was obtained from 16 mining and agricultural companies in the 2019-2021 period. This research method uses a panel data approach, namely the Random Effects Model. Data processing in this study uses Eviews 12. Based on the results of data processing, the data showed a significant negative influence between the Green Accounting variable (X) on Profit (Y). The causes of these negative impacts may involve additional investment in environmentally friendly practices, compliance with stringent environmental regulations, and additional operational costs associated with environmental conservation efforts